THE INFLUENCE OF HUMIC NATURE SUBSTANCES ON THE QUALITY OF SPERM PRODUCTION IN BREEDING BOARS DURING HEAT STRESS - Stepchenko, L.M.; Galyzina, L.I.; Pavlova, I.V.; Shostya, A.M.; Kravchenko, O.I.; Maslak, M.M. (Scientific Progress & Innovations, 2019)
The current state in pig breeding requires the optimization and full disclosure of animals’ potential while using biologically not harmful and environmentally safe substances. One of such substances is a biologically active additive of humic nature, which is made from environmentally pure Ukrainian peat by acid-alkaline extraction. The aim of the study was to determine the effect of humic substances on sperm production of breeding boars during heat stress, in particular, semen production quality and sperm morphometric indices. 10 adult breeding boars 18−24 months of age, five of which were of Poltava meat breed −group I and five the Red-White belted meat breed − group II, analogues by age, live weight, and the quality of sperm produc-tion, were selected for the experiment . Biologically active additive of humic nature was added in the feed during heat stress. The studies were conducted using the group-period method. The duration of the experi-ment was 100 days, in particular: the 1st period - preparatory for 30 days, the 2nd period − basic for 40 days and the 3rd period − final for 30 days. The mode of sexual loading was − receiving ejaculate twice a week. The breeding boars were placed individually. Sperm was received by the manual method. It has been deter-mined that heat stress reduces the quality of sperm production in boars. Giving feed additive of humic nature activates the processes of spermatogenesis, probably increasing the sperm concentration by 9.8 % in ani-mals of the Poltava meat and 13.3 % of the Red-White belted breeds. It has been found that the animals of the first breed were characterized by significantly higher sperm motility and survival, respectively, by 6.7% and 24.1 % (on the 30th day) and 10.8 and 14.6 % (on the 60th day of the experiment) as compared with the second breed. It has been established that heat stress for 30 days negatively affects the morphometric index-es of spermatozoa in the direction of significant reducing width and head area by 23.6 % (p<0.01) and 76.1 % (p<0.001) (group I) and 25.0 % (p<0.001) and 75.1 % (p<0.001) (group II). Giving feed additive of humic nature to breeding boars for 60 days levels the effect of negative factor.